2022
DOI: 10.5194/egusphere-2022-214
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Arctic sea ice radar freeboard retrieval from ERS-2 using altimetry: Toward sea ice thickness observation from 1995 to 2021

Abstract: Abstract. Sea ice volume significant interannual variability requires long-term series of observations to identify trends in its evolution. Despite improvements in sea ice thickness estimations from altimetry during the past few years thanks to CryoSat-2 and ICESat-2, former ESA radar altimetry missions such as Envisat and especially ERS-1 and ERS-2 have remained under-exploited so far. Although solutions have already been proposed to ensure continuity of measurements between CryoSat-2 and Envisat, there is no… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Furthermore, this will increase the uncertainty of sea ice thickness based on conventional altimeters such as HY-2B. Fortunately, some studies have shown that the sea ice thickness deviation between the traditional altimeter and the CryoSat-2 SAR altimeter can be improved by correction [56][57][58][59]. In the future, we will study the influence of HY-2B sea ice identification results on sea ice thickness deviation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this will increase the uncertainty of sea ice thickness based on conventional altimeters such as HY-2B. Fortunately, some studies have shown that the sea ice thickness deviation between the traditional altimeter and the CryoSat-2 SAR altimeter can be improved by correction [56][57][58][59]. In the future, we will study the influence of HY-2B sea ice identification results on sea ice thickness deviation.…”
Section: Discussionmentioning
confidence: 99%
“…For sea ice thickness, we utilized altimetry-based ice thickness retrievals from 1994 to 2022, as provided by (Bocquet, 2023;Bocquet & Fleury, 2024). This dataset integrates yearround 12.5 km gridded radar freeboard time series from ERS-1, ERS-2, Envisat, and CryoSat-2 missions.…”
Section: Datamentioning
confidence: 99%
“…This can lead to noticeable error in terms of the actual sea ice thickness. Therefore, we followed methods used in previous studies that resampled data over IMB tracks (Bocquet et al, 2022;Kwok et al, 2007;Mu et al, 2018;Stroeve et al, 2020;Xie et al, 2018).…”
Section: Data Griddingmentioning
confidence: 99%